Pengaruh Penerapan Good Governance, Audit Kinerja, Dan Standar Akuntansi Pemerintahan Terhadap Akuntabilitas Keuangan Pemerintah Daerah(Studi Kasus Pada Satuan Kerja Perangkat Daerah Kota Surakarta) - Rinaldi, Rizal Ricky; , Drs. Atwal Arifin, M.Si, Akt, CA (2016)
The study aimed to find out the effect of good governance on the financial accountability, the effect of performance audit on the financial accountability, and the effect of accounting standars of government on the financial accountability. This was a quantitative study conducted on the unit of local devices Surakarta regency, because the data collected in the forms of figures. The samples were determined proportionally on each unit of local devices (SKPD) based on the purposive sampling techniques. The analysis was made based on multiple linear regression supported by SPSS v.21 program. The results indicated that good governance had a positive and significant effect on the financial accountability, performance audit had a positive and significant effect on the financial accountability, and accounting standars of government had a positive and significant effect on the financial accountability.